DISTRIBUTION AND SALE OF ALCOHOLIC DRINKS IN REGIONAL REGULATION OF KAPUAS REGENCY NUMBER: 3 OF 2011 (STUDY OF SHARIA ECONOMIC LAW ANALYSIS) - Imro Atut Toyyibah; Muhammad Sodiki; Hendra Hadi; Parman Komarudin (Darussalam, 2023)
AbstractThis research has a background because the circulation of alcoholic beverages in Indonesia is increasingly widespread and widespread. Not infrequently the existence of alcoholic beverages often causes problems in society. The type of research is library research. The type of data used in this research is qualitative. The results of this study are that Islam prohibits or forbids the sale and purchase or trade of alcoholic beverages. Even Allah swt cursed drinkers, waiters, sellers, and even buyers of these alcoholic drinks. Even though in the Kapuas Regency Regional Regulation Number: 3 of 2011, it has given permission to certain individuals or groups to sell or trade these alcoholic drinks. The prohibition of buying and selling alcoholic beverages is due to the fact that the goods traded or traded belong to goods that are forbidden to be used as a business in Islam. Keywords: Alcoholic beverages; Regional Regulations; Buy and sell.